Pemusatan Perhatian (Mindfullness) dengan Pendekatan melalui Senam Yoga terhadap Kualitas Hidup pada Pasien Halusinasi - Aisyah Salsabila Nur’azizah; Wita Oktaviana; Pudji Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of mindfulness through yoga on the quality of life of patients with hallucinations. The study used a case study design with a one-group pretest-posttest approach. The results showed that before the intervention, respondents' quality of life was in the poor to moderate category, with scores ranging from 26–58. After the intervention, all respondents experienced an improvement in their quality of life, ranging from good to excellent, with scores ranging from 69–84. These changes were demonstrated by decreased anxiety, increased control over hallucinations, emotional stability, improved social interactions, and the ability to carry out daily activities. In conclusion, mindfulness through yoga is effective in improving the quality of life of patients with hallucinations. Keywords: Hallucinations, Quality of Life, Mindfulness, Schizophrenia, Yoga